Therapeutic relevance of SOX9 stem cell factor in gastric cancer. (1st February 2019) - Carrasco-Garcia, Estefania; Álvarez-Satta, María; García-Puga, Mikel; Ribeiro, Marcelo Lima; Arevalo, Sara; Arauzo-Bravo, Marcos; Matheu, Ander
ABSTRACT: Introduction : Recent comprehensive genetic and molecular profiling has identified molecular subtypes of gastric cancer (GC) and has linked them to clinical information. Moreover, SOX9 has been recently described as a relevant regulator of the population of GC stem cells (gCSCs), which are responsible for GC initiation and progression. Areas covered : Through public data from The Cancer Genome Atlas (TCGA) project, the Asian Cancer Research Group (ACRG) and published studies, we link SOX9 expression to GC clinical information and molecular subtypes. We also discuss the role of deregulated SOX9 activity in critical aspects of GC progression, as well as therapy resistance. Finally, we provide information of the molecular mechanisms associated with its oncogenic activity. Expert opinion : This review presents the clinical impact of SOX9 in GC and underscores the molecular mechanisms associated with its oncogenic activity. Current evidence highlights the key function of SOX9 in GC and postulates it as a prognostic factor, novel biomarker for patient stratification and a promising target. gCSCs are critical targets for GC eradication and SOX9 is a regulator of gCSCs; hence, the inhibition of SOX9 is a potential therapeutic strategy for GC, particularly for the MSS/TP53+ subgroup of patients in whom SOX9 expression correlates with poor outcome.